Titanium isopropoxide complexes containing diamine bis-thiolato based [N2S2](2-) ligands; effect of steric bulk on coordination features - Shaban, Shaban Y.; Ramadan, Abd El-Motaleb M.; Heinemann, Frank Wilhelm (Inorganic Chemistry Communications, 2012)
Two dianionic amine bis(thiolato) ligands are introduced and their reactions with titanium tetra(iso-propoxide) studied; ligand N2H2S2 - H-2 (1) having NH donor groups leads exclusively to dinuclear [Ti(N2H2S2)((OPr)-Pr-i)(2)] (2) along with an oxidation product of the ligand (3) whereas ligand N2Me2S2 - H-2 (4) having an additional N-substituent leads exclusively to a mononuclear [Ti(N2Me2S2)((OPr)-Pr-i)(2))] (5) type complex. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Titanium complexes; Structure; Bis-thiolato complexes; Amide coordination; Thiolate oxidation; Hydrolysis